A Brief Exploratory Report of Coping Strategies Among Police Recruits During Academy Training. Issue 2 (October 2016) - Patterson, George T.
Few longitudinal studies have investigated the use of coping strategies among police recruits. This study investigated perceived life and work stressors, appraisal, and coping over a seven-month police recruit academy training program. Participants were 81 police recruits who completed the Ways of Coping Questionnaire at three time points approximately three months apart. The average age of the recruits was 27.6 years ( SD  = 5.1, range 20–51). Separate repeated measures analyses of variance were conducted to examine coping scores. Statistically significant decreases, although small, were observed in reported emotion-focused, problem-focused, and seeking social support coping strategies. Results suggested that as police recruits undergo academy training, they rely on fewer coping strategies to deal with life and work stress. More longitudinal studies are needed that assess the methods police recruits utilize to manage stress during academy training. Such results can inform stress management interventions.